Influence of Exogenous Ethylene and Mechanical Damage on Gene Expression and Physiological Parameters of Maize Hybrids - Péter Makleit; Gabriella Gulyás; Levente Czeglédi; Szilvia Veres (Agronomy, 2024)
This study investigated the responses of two maize hybrids, Armagnac and Desszert R-78, to exogenous ethylene and mechanical damage as stress treatments. The amounts of benzoxazinoids (BXDs) and malondialdehyde (MDA) and the activities of superoxide dismutase (SOD) and catalase (CAT) were examined 2 and 4 h after ethylene and mechanical damage treatments as well as at the age of 24 days, and the activity of genes encoding BXD biosynthesis and other stress-related genes was measured in shoots. In both hybrids, mechanical damage upregulated the genes responsible for the synthesis of BXDs (BX8 and BX9), the AOC1 gene encoding jasmonate, and the DEH gene encoding lipid biosynthesis enzymes. Significant genotype differences were found in the amounts of BXDs. In the case of the Desszert R-78 hybrid, the BXDs level was increased at 4 h after stress treatments compared to the control. In the case of the Armagnac hybrid, the amount of BXDs decreased in response to ethylene compared to the control. The absence/presence of a correlation between the activity of genes encoding BXDs and the amount of BXDs is thought to be due to the different rate/speed of the response in the two hybrids. Mechanical damage and ethylene treatments did not significantly affect the activities of SOD and CAT as well as the amount of MDA during the four-hour study period.